Sahnya Perjanjian Kawin Dalam Perkawinan Beda Agama Di Indonesia - Ari Tri Wibowo (Fakultas Hukum Universitas Islam Malang, 2023)
The increasing prevalence of interfaith marriages in Indonesia does not rule out the possibility of making a marriage agreement both before and during the marriage, this research attempts to decipher the validity of the agreement made. The type of research used is normative research using a normative juridical approach. Legal materials were collected by literature study and document study, the results of the study concluded that the validity of interfaith marriages depended on court decisions and then registration of marriages at the Civil Registry Office, then the validity of the marriage agreement made in interfaith marriages was determined by the validity of the marriage different religions are carried out, if the interfaith marriage is legal then the agreement can be said to be valid as a marriage agreement but conversely if the interfaith marriage is invalid then the marriage agreement made will be considered as an agreement in general.